Survival in Sarajevo - How a Jewish Community Came to the Aid of Its City
This short film is an exploration of the contemporary relationship between Europe and the Jews who remained within its borders. Through images from besieged Bosnia, photojournalist Edward Serotta tells the story of the remaining Jews in Sarajevo.